The Chikungunya anxiety scale (CHIKAS): Development, validation, and relationship between its items and illness-related factors - Júlio Torales; Iván Barrios; Gladys Estigarribia; Guillermo Sequera; José Almirón‐Santacruz; Marcelo O’Higgins; Rodrigo Navarro; Osvaldo Melgarejo; Israel González; Tomás Caycho‐Rodríguez; João Maurício Castaldelli-Maia; Antonio Ventriglio; et al. (2023)
Background: Paraguay has recently experienced an exponential increase in chikungunya cases, leading to psychological distress, particularly anxiety. Aim: To develop and validate the Chikungunya Anxiety Scale (CHIKAS). Materials and Methods: An initial scale of 18 items was used, which was subjected to validation by expert judgment to obtain 14 items. To determine construct validity, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) have been employed, and internal and convergent validity were determined. Demographic, socioeconomic, and health status data were also collected. Results: The study included 974 participants. The final scale consisted of 12 items with evidence of a two-factor model (psychological and physical). The internal validity was good (McDonald's omega = 0.882). The CFA showed good adjustment indices. Regarding participant characteristics, a relationship was found between anxiety due to chikungunya and gender, employment, mental diagnosis, medication use, and chikungunya infection. Conclusion: The final 12-item CHIKAS had strong psychometric properties and was a two-factor model.